Team physician challenges in 2013: dealing with media and travelling across state borders - Olson, D. E. (British Journal of Sports Medicine, 2013)
In the modern world it is imperative to understand the social and legal aspects of caring for the athlete. Two recent BJSM articles highlight important aspects of team physician practice. Confidentiality and protection of athletes medical information is increasingly challenging in the era of social media, which allows rapid dissemination of individuals` personal details from a variety of sources. Additionally, as physicians travel both domestically and internationally to cover events, it is important to consider legal and social aspects of caring for the athlete. These may include: licensing issues, malpractice coverage, access to care at outside institutions and prescribing medications, including narcotics. As healthcare evolves in the USA and across the world, it is important for the team physician to be updated on the latest policies and factors, which may prevent them from providing necessary care in a timely fashion.